PENGARUH PERSEPSI KEAMANAN DAN KERAHASIAAN TERHADAP NIAT MEMBAYAR PAJAK MENGGUNAKAN PAJAKPAY - Dewi Kusuma Wardani; Nur Anita Chandra Putry; Fitri Aprilia Kusuma Dewi (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
This studys aims to determine whether perceptions of security and confidentiality affect the intention to pay taxes using tax pay. This research data using direct / primary data. The sampling method is convenience sampling. The data analysis technique is path analysis with the perception of security and confidentiality as independent variables and the intention to pay taxes using tax pay as the dependent variable. The results of the analysis conclude that the perception of security and confidentiality has a positive effect on the intention to pay taxes using tax pay. The implication of this research proves that perceptions of security and confidentiality are the determining factors that encourage taxpayers' intention to pay taxes using the tax pay application.